Estabilização de uma estrutura de contenção por meio de estaqueamento a montante: uma análise paramétrica por meio da modelagem numérica tridimensional utilizando o RS3 - (:unkn) unknown (Universidade Federal do Pampa, 2026)
This study aimed to determine the stability of a bridge abutment through three-dimensional numerical modeling using the Rocscience RS3 software, employing micropiles as a reinforcement mechanism. The research is grounded in the growing need to understand the behavior of soil-structure interaction. The three-dimensional numerical model was developed based on the Finite Element Method (FEM), incorporating boundary conditions, constraints, and an analysis of the model's length and width, while maintaining a fixed depth of 10 meters based on the condition of the pile being anchored into the rock and utilizing different mesh types to determine conditions that would neither generate numerical inconsistencies nor bias the model. The numerical analysis allowed for the estimation of displacements and maximum stresses, as well as the identification of critical stress concentration zones, providing a technical basis for the design and sizing of stabilization solutions. Based on the obtained results, it was possible to quantify the horizontal displacements and stresses generated under each combination of the analyzed parameters and to produce graphical analyses. Through Analysis of Variance (ANOVA), it was possible to observe the variables that most influenced the model. The analyzed horizontal stresses showed low sensitivity to changes in the evaluated parameters; regarding horizontal displacements, however, a greater influence of geometric variables was observed. It is expected that the obtained results contribute to the practical application of numerical methods in stability studies, promoting greater reliability and durability for construction structures. Keywords: Slope stability, numerical modeling, RS3.
Keywords: Engenharia civil; Estabilidade de taludes; Modelagem numérica; RS3; Civil engineering; Slope stability; Numerical modeling; ENGENHARIAS